Feasibility Study of Raw Material for Hybrid Power Plant in Coastal Cilacap Selatan - Afrizal Abdi Musyafiq; Vicky Prasetia; Purwiyanto Purwiyanto; Hera Susanti; Novita Asma Ilahi; Hendi Purnata; Saepul Rahmat (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2022)
Cilacap Regency is a coastal area south of the island of Java. The purpose of this study is to determine the potential of raw materials available in the South Cilacap Coastal area and to determine the potential power that can be generated for the PLTH system through the calculation of the raw material data that has been obtained. This research method begins with direct measurements of wind speed and light intensity. Both devices read data in real time and connect online. The data obtained is processed to determine the wind speed and the average intensity of sunlight. The results of these calculations are entered into the equations to calculate the potential power that can be generated. Based on the calculation, the average wind speed is 3-4 m/s and the light intensity is 54612 watt/m2. The results of the calculation of the potential power that can be generated from the PLTB system in the coastal area of ??South Cilacap is equivalent to 508 watts/day. The potential power that can be generated from PLTS is 10.8 kW/day. The total potential power that can be generated from the PLTH system on the coast of South Cilacap is equivalent to 273.22 kWh/day.